2005
DOI: 10.1182/blood-2004-09-3683
|View full text |Cite
|
Sign up to set email alerts
|

B-Raf–dependent expression of vascular endothelial growth factor–A in Kaposi sarcoma–associated herpesvirus-infected human B cells

Abstract: IntroductionKaposi sarcoma-associated herpesvirus/human herpesvirus 8 (KSHV/HHV-8) is the latest addition to the list of human herpesviruses. KSHV was first isolated from Kaposi sarcoma (KS) lesions in persons suffering from acquired immunodeficiency syndrome (AIDS) in 1994. 1 The cancerous conditions that are etiologically associated with KSHV are KS, primary effusion lymphoma (PEL), and multicentric Castleman disease (MCD). 2 Apart from the inflammatory cytokines (ICs)/growth factors (GFs), lytic KSHV infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 43 publications
0
41
0
Order By: Relevance
“…Similarly, Akula et al (31) showed that 1 h of treatment of HHV8-infected B cells with 50 Amol/L PD98059, another MEK1/2 inhibitor (32), causes a substantial decrease in levels of VEGF mRNA and protein. These observations indicate that, although MKK signaling is an important regulator of VEGF release, some aspects of its control may be cell type specific.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Akula et al (31) showed that 1 h of treatment of HHV8-infected B cells with 50 Amol/L PD98059, another MEK1/2 inhibitor (32), causes a substantial decrease in levels of VEGF mRNA and protein. These observations indicate that, although MKK signaling is an important regulator of VEGF release, some aspects of its control may be cell type specific.…”
Section: Discussionmentioning
confidence: 99%
“…Akula et al [36] demonstrated that VEGF expression by HHV-8 -infected human B cells is mediated by the RAF pathway and that VEGF production can be aborted by using a mitogen-activated protein kinase/extracellular signalrelated kinase kinase inhibitor [36]. Understanding whether the RAF pathway plays an essential role in the mechanism of CD requires further research.…”
Section: Other Signaling Pathway Effectors: Stat Raf and Calcineurinmentioning
confidence: 99%
“…Additionally, our data do not exclude the possibility that KSHV induction of 14-3-3␤ expression influences other genes which themselves regulate DUSP1 expression, cytokine expression, and/or endothelial cell invasiveness. For example, published data indicate that 14-3-3␤ facilitates Raf/Ras activation through the coupling of protein kinase C-to Raf-1 (71), and we and others have demonstrated that KSHV induction of ERK-dependent VEGF expression and endothelial cell invasiveness are due, in part, to KSHV regulation of Ras/Raf activation (34,72). Furthermore, the mechanisms through which xCT induces 14-3-3␤ expression require additional clarification.…”
Section: Discussionmentioning
confidence: 99%